2000
DOI: 10.1017/s0016756800003484
|View full text |Cite
|
Sign up to set email alerts
|

Conodont biozonation in the upper Arenig of Sweden

Abstract: Conodont faunas from the Arenigian Lanna/Volkhov Stage in Baltoscandia have been the subject of intensive study, particularly during the last decade, and different biozonations based on them have been proposed. The application of some of these zones is discussed here. The present investigation is mainly based on 64 samples from ten sections in Sweden, but conodont collections from Bornholm (Denmark) and Tamsalu (Estonia) have also been studied. Lindström's (1971) concept of the upper Arenigian Microzarkodina p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Bagnoli & Stouge (1997) subdivided the overlying interval into a lower B. norrlandicus Zone and an upper Lenodus antivariabilis Zone. Trapezognathus quadrangulum, which has its last occurrence in their lower zone, is present in all three samples representing the B. norrlandicus Zone at Mäekalda (Mä95-30, -31 and -38), the entire thickness of which is less than 0.3 m. It can thus be concluded that the uppermost Volkhov-lowermost Kundan L. antivariabilis Zone of Bagnoli & Stouge (1997), or the L. antivariabilis Subzone sensu Löfgren (2000a), is lacking in the section. Between samples Mä95-38 and Mä95-37, at the boundary between the Lahepere Member of the Toila Formation and the Kallaste Member of the Pakri Formation, there is thus a considerable stratigraphic gap in the succession, since the basal Pakri includes at most 0.1 m of the combined upper Volkhov-lower Kunda up to the base of the Eoplacognathus pseudoplanus Zone represented by sample Mä95-35.…”
Section: Conodont Biozonationmentioning
confidence: 86%
See 3 more Smart Citations
“…Bagnoli & Stouge (1997) subdivided the overlying interval into a lower B. norrlandicus Zone and an upper Lenodus antivariabilis Zone. Trapezognathus quadrangulum, which has its last occurrence in their lower zone, is present in all three samples representing the B. norrlandicus Zone at Mäekalda (Mä95-30, -31 and -38), the entire thickness of which is less than 0.3 m. It can thus be concluded that the uppermost Volkhov-lowermost Kundan L. antivariabilis Zone of Bagnoli & Stouge (1997), or the L. antivariabilis Subzone sensu Löfgren (2000a), is lacking in the section. Between samples Mä95-38 and Mä95-37, at the boundary between the Lahepere Member of the Toila Formation and the Kallaste Member of the Pakri Formation, there is thus a considerable stratigraphic gap in the succession, since the basal Pakri includes at most 0.1 m of the combined upper Volkhov-lower Kunda up to the base of the Eoplacognathus pseudoplanus Zone represented by sample Mä95-35.…”
Section: Conodont Biozonationmentioning
confidence: 86%
“…This is indicative of the base of the B. norrlandicus Zone sensu Bagnoli & Stouge (1997) and Löfgren (2000a), which is thus situated in the middle part of the Lahepere Member. Bagnoli & Stouge (1997) subdivided the overlying interval into a lower B. norrlandicus Zone and an upper Lenodus antivariabilis Zone.…”
Section: Conodont Biozonationmentioning
confidence: 89%
See 2 more Smart Citations
“…The stratigraphic distribution of Conchoprimitia species from the Floian to lower Darriwilian (Billingen, Volkhov and Kunda regional stages) of Baltoscandia is presented in Table 1. Conchoprimitia is (Löfgren 1995(Löfgren , 2000Nõlvak et al 2006). Data for Västergötland from Jaanusson (1982) and Dronov et al (2001); Oslo region from Owen et al (1990).…”
mentioning
confidence: 99%